New insights into the phylogeny and skull evolution of stegosaurian dinosaurs: An extraordinary cranium from the European Late Jurassic (Dinosauria: Stegosauria) - Sergio Sánchez-Fenollosa; Alberto Cobos (Vertebrate Zoology)
Abstract Stegosauria is an iconic clade of thyreophoran dinosaurs mainly characterized by two parasagittal rows of osteoderms that extend from the neck to the end of the tail. The fossil record of stegosaurian cranial material is remarkably fragmentary and scarce. This study describes the most complete stegosaurian skull from Europe and proposes a new hypothesis for the phylogenetic relationships of stegosaurs. This new cranial material was recovered from beds of the Villar del Arzobispo Formation (Upper Jurassic, Teruel, Spain) and is confidently referred to Dacentrurus armatus. It provides valuable insights into the anatomy of this species and enhances the understanding of skull evolution in stegosaurs. Furthermore, the diagnosis of D. armatus is updated with the identification of a new autapomorphy. Stegosaurian phylogenetic nomenclature is also revised. Maximum Parsimony has been applied to analyse a new stegosaurian data matrix. Phylogenetic analyses suggest that Stegosauria is divided into two major clades: Huayangosauridae and Stegosauridae. These analyses support Isaberrysaura mollensis as a stegosaur and place it within Huayangosauridae, a clade that also includes several Jurassic stegosaurs from Asia. For the first time, Mongolostegus exspectabilis is included in a phylogenetic analysis, the results of which suggests that a lineage of huayangosaurids or early-diverging stegosaurids persisted in Asia until at least the late Early Cretaceous. The new tree topologies challenge the synonymization of the genera Stegosaurus and Wuerhosaurus. Moreover, it is concluded that a taxonomic re-evaluation of Early Cretaceous Chinese stegosaurs is necessary. Alcovasaurus longispinus and Kentrosaurus aethiopicus are recovered as dacentrurines.